2015
DOI: 10.3233/wor-152168
|View full text |Cite
|
Sign up to set email alerts
|

Implications of sit-stand and active workstations to counteract the adverse effects of sedentary work: A comprehensive review

Abstract: Based on these preliminary data from 26 studies, conducting large scale randomized controlled trials with ergonomic training as their essential component is recommended to understand the benefits of sit-stand workstations for prevention of sedentary work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 47 publications
1
23
0
1
Order By: Relevance
“…Several studies have identified that cognitive performance is not impaired by short-term use of these workstations (working while standing, or while walking at low intensity) [8, 16, 37, 38], indicating that using these devices do not compromise employees´ work-related productivity if there is a good alignment with job tasks [12–14]. While Tudor-Locke et al (2014) [7] indicated that little was known about the impact of learning or adaptation on using active workstations on employees´ work productivity, W@WS now offers preliminary evidence of sustained positive work-oriented outcomes linked to using “sit less, move more” programs during working hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified that cognitive performance is not impaired by short-term use of these workstations (working while standing, or while walking at low intensity) [8, 16, 37, 38], indicating that using these devices do not compromise employees´ work-related productivity if there is a good alignment with job tasks [12–14]. While Tudor-Locke et al (2014) [7] indicated that little was known about the impact of learning or adaptation on using active workstations on employees´ work productivity, W@WS now offers preliminary evidence of sustained positive work-oriented outcomes linked to using “sit less, move more” programs during working hours.…”
Section: Discussionmentioning
confidence: 99%
“…However, standing and treadmill desk-based or ‘sit less and move more’ workplace interventions have showed mixed results for improving psychological well-being with little or no impact on work productivity [1520]. Most research has investigated whether using active workstations in the office maintains employee performance, rather than enhancing employee productivity [8, 12, 14, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…No other environmental or behavioural interventions were employed to promote physical activity or encourage the participant's use of EAHDs. Several studies [65][66][67] have noted a significant decrease in sitting times associated with ergonomics awareness. In contrast, although Straker et al [39] found modest decreases in sitting time associated with AHDs, no significant differences were found with 'ergonomics awareness training', analogous to education/information provision.…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews have confirmed the importance of active workstations in counteracting the effects of sedentary work (9,15). They have highlighted that some amount of standing in an 8-hour work period was beneficial and that active workstations can increase Additional Supporting Information may be found in the online version of this article.…”
Section: Introductionmentioning
confidence: 99%